1999
DOI: 10.1034/j.1399-3054.1999.106109.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al on the phytosiderophore‐mediated solubilization of Fe and uptake of Fe‐phytosiderophore complex in wheat (Triticum aestivum)

Abstract: The effect of Aluminum (Al) on phytosiderophore‐mediated solubilization of insoluble Fe and the uptake of phytosiderophore‐Fe3+ complex was examined in wheat (Triticum aestivum L. cv. Atlas 66). Al addition did not affect the Fe solubilization by 2′‐deoxymugineic acid (DMA), although Cu addition significantly inhibited the solubilization capacity. Addition of ten times more Al than Fe to the solution of DMA‐Fe3+ complex did not decrease the absorption of the DMA‐Fe3+ complex at 375 nm. Furthermore, NMR study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The equilibrium formation constant for the dehydrated Al(III)-MA complex has been reported to be smaller than that of the corresponding Fe(III) complex by a factor between 10 6 and 10 8 (Murakami et al 1989), although the thermodynamic formation constants have not been reported. Furthermore, no interaction between Al(III) and MA has been reported on the basis of either physiological or NMR investigations (Chang et al 1988). It is important to clarify whether MAs and NA bind Al(III) under physiological conditions in order to generate a clear understanding of trivalent metal metabolism in higher plants.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium formation constant for the dehydrated Al(III)-MA complex has been reported to be smaller than that of the corresponding Fe(III) complex by a factor between 10 6 and 10 8 (Murakami et al 1989), although the thermodynamic formation constants have not been reported. Furthermore, no interaction between Al(III) and MA has been reported on the basis of either physiological or NMR investigations (Chang et al 1988). It is important to clarify whether MAs and NA bind Al(III) under physiological conditions in order to generate a clear understanding of trivalent metal metabolism in higher plants.…”
Section: Introductionmentioning
confidence: 99%